1987
DOI: 10.1007/bf02887574
|View full text |Cite
|
Sign up to set email alerts
|

Storage ofCandida albicans, C. tropicalis and related species in liquid nitrogen

Abstract: Storage in liquid nitrogen of a collection of C. albicans, C. tropicalis and related species checked by numerical and classical taxonomy is described. Strains stored for 3 years in liquid nitrogen were thawed and their survival was tested. After adaptation and regeneration, their fermentation and assimilation spectra, production of chlamydospores and pseudomycelia, appearance and radial growth rate of giant colonies were investigated and compared with the properties of cultures stored under paraffin oil. It fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Later, a study of cryopreservation of C. albicans , Candida aldoi, Candida claussenii, Candida stellatoidea, C. tropicalis and Candida intermedia was published (Breierova et al., 1987). A total of 26 strains were studied, using yeast extract, peptone, brewing wort, and dimethyl sulfoxide as cryoprotectant agent formulation.…”
Section: Available Techniques For Preservation Of Non‐saccharomyces Y...mentioning
confidence: 99%
“…Later, a study of cryopreservation of C. albicans , Candida aldoi, Candida claussenii, Candida stellatoidea, C. tropicalis and Candida intermedia was published (Breierova et al., 1987). A total of 26 strains were studied, using yeast extract, peptone, brewing wort, and dimethyl sulfoxide as cryoprotectant agent formulation.…”
Section: Available Techniques For Preservation Of Non‐saccharomyces Y...mentioning
confidence: 99%
“…Concerning the genus Malassezia spp., their low in vitro viability represents the main obstacle for retrospective and prospective studies, as reported by several authors. 1,6,7 Thus, the development of an efficient methodology for the preservation of zygomycetes and Malassezia spp. is of great importance for the development of prospective studies with these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them more vulnerable to mechanical damages, including those caused by ice crystals. Concerning the genus Malassezia spp., their low in vitro viability represents the main obstacle for retrospective and prospective studies, as reported by several authors 1,6,7 . Thus, the development of an efficient methodology for the preservation of zygomycetes and Malassezia spp.…”
Section: Introductionmentioning
confidence: 99%